Foresight analysis informs strategic decision making of countries, CGIAR and the donor community - CGIAR Research Program on Policies, Institutions, and Markets (2019)
The PIM-led CGIAR foresight modeling team has provided valuable insights to assist decision makers and other decision makers in assessing the consequences of alternative policies and investments on human well-being. A recent external review highlights many cases of PIM foresight outputs being used in support of global, regional and national decisions.